ChemInform Abstract: Chemical Insight into the Mechanism and Specificity of GlfT2, a Bifunctional Galactofuranosyltransferase from Mycobacteria. Issue 45 (October 2016) - Poulin, Myles B.; Lowary, Todd L.
Abstract: Review: 56 refs.